Pustulotic arthro-osteitis (Sonozaki Syndrome) - Ozlem Su; Serpil Pirmit; Dilek Biyik Ozkaya; Yasemin Balsever Kural; Nahide Onsun (Wolters Kluwer Medknow Publications, 2011)
Pustulotic arthro-osteitis, first described by Sonozaki, is a relatively rare disorder. Its prevalence is however probably underestimated in dermatological literature. Early recognition of the signs can prevent misdiagnosis. We describe a Turkish patient who presented with palmoplantar pustulosis and involvement of the sternoclavicular joint and peripheral oligoarthritis.